An in vitro investigation of the antidermatophytic, antioxidant, and nephroprotective activity of Solanum surattense. (October 2021) - Narayanan, Mathiyazhagan; Jayashree, Thangaraj; Kandasamy, Sabariswaran; Natarajan, Devarajan; Liu, Guanglong; Elesawy, Basem H.; Elfasakhany, Ashraf; Pugazhendhi, Arivalagan
Graphical abstract: Highlights: This is the first study on Solanum surattense against dermatophytic fungi. Methanol extract has a higher volume of phytochemicals than others extracts. S. surattense methanol extract active against C. albicans, E. floccosum, T. rubrum. The DPPH and Hydroxyl radical scavenging were successful at 83.15 & 89.95 %. On HEK 293 cells, methanol extract has significant nephroprotective (95.31 %). Abstract: The phytochemical, antidermatophytic, antioxidant, and nephroprotective properties of the aboveground parts of the traditional medicinal plant Solanum surattense were investigated. The methanolic extract alone had a higher concentration of phytochemicals than other extracts. The hole-plate diffusion method revealed that the methanolic extract had significant antidermatophytic activity against Trichophyton rubrum, Candida albicans, and Epidermophyton floccosum and comparable with nystatin. It also demonstrated excellent antioxidant activity, 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and hydroxyl radical scavenging activities comparable to standard antioxidants. Moreover, the methanolic extract demonstrated outstanding nephroprotection on the Human Embryonic Kidney (HEK 293) cell line when tested with cisplatin using the (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. The increased concentration (500 g mL −1 ) of the crude methanolic extract effectively protected (95.31 %) the HEK 293 cells from cisplatin nephrotoxic activity, and it was comparable with rutin (98.5 %) drug. These findings suggested that the methanolic extract ingredients could be used for a variety of medicinal purposes.